Starting a Family: Characteristics Associated With Men's Reproductive Preferences. (May 2013) - Kessler, Lawrence M.; Craig, Benjamin M.; Saigal, Christopher; Quinn, Gwendolyn P.
Compared with previous generations in the United States, men today are starting families later in life and having fewer children. As a result birthrates in the United States have dropped sharply, and some men never make the transition into parenthood. Using data from the 2006-2010 National Survey of Family Growth, this study examines the characteristics of childless men in the United States between the ages of 15 and 44 ( N = 6, 168) and whether these men want to have a child sometime in the future. Our main finding is that the majority of childless men want a child someday; however, by the age of 45 more than 1 in 7 still remain childless.